Crystalloid Administration Is Associated with the Recovery of Pediatric Elective Roux-en-Y Hepaticojejunostomy - Tan, Xingqin; Liu, Jianxia; Guo, Chunbao (European Journal of Pediatric Surgery, 2020)
Introduction Intraoperative fluid administration is important for postoperative recovery and might be associated with postoperative complications.Materials and Methods This retrospective review included 471 patients who underwent Roux-en-Y hepaticojejunostomy. Patients were separated into two groups based on whether they received low (<15.27 mL/kg/h) or high (>15.27 mL/kg/h) volumes of corrected crystalloid fluids. Propensity score matching was performed to adjust for any potential selection bios for the two groups. In 192 matched patients, clinical outcomes, including postoperative complications and length of hospital stay, were compared.Results Higher use of diuresis (p = 0.027) was found in the high fluid group. Receiving low volumes of crystalloids was associated with postoperative gastrointestinal functional recovery, reflected by the first defecation (odds ratio [OR], 0.69; 95% confidence interval [CI], 0.31–1.07; p = 0.047) and first bowel movement (OR, 0.56; 95% CI, 0.38–0.98; p = 0.013). However, the occurrence of renal complications did not show significant differences between the groups. A lower postoperative complication rate (OR, 0.54; 95% CI, 0.42–0.94; p = 0.016) was noted in patients with low crystalloids compared with high crystalloids. The total length of hospital stay was longer in patients with high crystalloid fluid (9.21 ± 3.24 days) than patients with low volumes (7.83 ± 2.58 days; p = 0.012).Conclusion Low crystalloid fluid administration was associated with favorable postoperative outcomes.
Keywords: crystalloid administration; length of hospital stay; abdominal surgery; acute kidney injury